Concluding Remarks in The Qur’anic Surahs: A Reflection - Prof Dr Israr Ahmad Khan (jihat-ul-islam, 2023)
The Qur’an is extraordinarily unparalleled speech of Allah, the Creator, the Sustainer, the Provider, the Controller of the universe, the Counsellor. Its words, sentences, statements, admonitions, and commands are all very effective to the readers and the audience. The main reason for it being so appealing to human heart is its marvelous eloquence (balaghah). An eloquent speech, for sure, comprises fundamentally four components: (1) preface, (2) central theme, (3) contextual flow, and (4) conclusion. The speech will stand deprived of eloquence in case any of these elements is missing therein. The Qur’an as the most remarkable speech as to its eloquence. It simply means that the Qur’anic chapters (suwar) contains all the features of eloquence, including Conclusion. This paper represents a humble reflection on the Conclusion of some selected Qur’anic chapters, such as Surah al-Baqarah, Surah Aali ‘Imran, Surah al Nisa’, Surah al-Ma’idah, Surah al-n‘am, Surah al-A‘raf, Surah al-Anfal, Surah al-Tawbah. The task to be carried out in the paper is (1) identification of the verses deemed to be Conclusion in the Surah, (2) reflection on its relationship with the subject-matter/s discussed in the Surah. The methodology applied in the paper is reflection (tadabbur) and critical analysis (ta‘aqqul). The end-result of the discussion is that the Concluding Remarks in the Qur’anic Surahs serve as the venue for very cohesive and coherent messages from Allah.